Diabetes Increases the Vulnerability of the Cardiac Mitochondrial Network to Criticality - Vetter, Larissa; Cortassa, Sonia; O’Rourke, Brian; Armoundas, Antonis A.; Bedja, Djahida; Jende, Johann M. E.; Bendszus, Martin; Paolocci, Nazareno; Sollot, Steven J.; Aon, Miguel A.; Kurz, Felix T. (Frontiers in Physiology, 2020)
Mitochondrial criticality describes a state in which the mitochondrial cardiac network under intense oxidative stress becomes very sensitive to small perturbations, leading from local to cell-wide depolarization and synchronized oscillations that may escalate to the myocardial syncytium generating arrhythmias. Herein, we describe the occurrence of mitochondrial criticality in the chronic setting of a metabolic disorder, type 1 diabetes (T1DM), using a streptozotocin (STZ)-treated guinea pig (GP) animal model. Using wavelet analysis of mitochondrial networks from two-photon microscopy imaging of cardiac myocytes loaded with a fluorescent probe of the mitochondrial membrane potential, we show that cardiomyocytes from T1DM GPs are closer to criticality, making them more vulnerable to cell-wide mitochondrial oscillations as can be judged by the latency period to trigger oscillations after a laser flash perturbation, and their propensity to oscillate. Insulin treatment of T1DM GPs rescued cardiac myocytes to sham control levels of susceptibility, a protective condition that could also be attained with interventions leading to improvement of the cellular redox environment such as preincubation of diabetic cardiac myocytes with the lipid palmitate or a cell-permeable form of glutathione, in the presence of glucose.